UPAYA PEMBERDAYAAN MASYARAKAT GILI INDAH DALAM PEMANFAATAN SAMPAH PLASTIK MENJADI Eco-Brick OLEH MAHASISWA KELOMPOK KKN UNRAM - Aji, Lalu Febrian Siswandi; Christie, Fleury; Sari, Baiq Davina Lolita; Magdalena, Magdalena; Abdat, Nilna Aulia; Adinata, Ahmad Farid; Safitri, Anggia Cahyani; Nurfitriyani, Nurfitriyani; Sukmawan , Raden; Rafiq, M (Jurnal Wicara, 2023)
Plastic waste is the largest contributor to waste on Earth. With the rapid development of industries and the production of various goods, whether they are food or other products, plastic waste is inevitable. Plastic waste takes a very long time to decompose, so when it accumulates, it becomes a waste that harms the natural ecosystem, both in the oceans and on land. The issues related to waste are concerning, especially in densely populated communities. With high population density comes a significant amount of waste and residue generated by the population.Sometimes, the lack of specific attention from the government regarding how to address plastic waste in society can lead to negative consequences. These consequences may include flooding, clogged waterways, and increased mosquito populations due to the accumulation of waste. This situation highlights the need to find solutions or alternatives to address the plastic waste problem in densely populated communities. Various solutions and alternatives could involve managing plastic waste to create valuable products, such as transforming it into eco-bricks that benefit society. Gili Indah Village is a tourist destination facing issues caused by the accumulation of household plastic waste. This situation presents an opportunity to address the waste problem. The KKN (Community Service Program) group from Mataram University is dedicated to providing solutions and contributions to the community in tackling the plastic waste issue by transforming it into eco-bricks.